Core-shell structure multiphase ceramic substrate and preparation method thereof

By adopting the preparation method of core-shell structure composite ceramic substrate, titanate precursor powder is synthesized using metal oxides and TiO2, and core-shell structure powder is formed through ultrasonic cleaning and microemulsion technology. Finally, the ceramic substrate is prepared by microwave sintering, which solves the problems of high dielectric loss and low breakdown strength of existing microwave dielectric ceramic materials, and realizes ceramic substrates with low dielectric loss, high breakdown strength and low sintering temperature.

CN119683993AActive Publication Date: 2025-03-25CHINA BUILDING MATERIALS ACADEMY CO LTD

Patent Information

Application Number
CN202411674050.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing microwave dielectric ceramic materials have high dielectric loss and low breakdown strength, which limits their application in modern communication technology.

Method used

The preparation method of core-shell structure composite ceramic substrate is used to perform ball milling and high-temperature molten salt reaction using metal oxides and TiO2 as raw materials, using anhydrous ethanol and NaCl-KCl molten salt to synthesize titanate precursor powder, and the core-shell structure powder is formed through ultrasonic cleaning and microemulsion technology, and the ceramic substrate is finally prepared by microwave sintering.

Benefits of technology

It significantly reduces the dielectric loss of the composite ceramic substrate, improves the breakdown strength, and reduces the sintering temperature, meeting the demands of electronic components for miniaturization, miniaturization and high performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005146609090000041
    Figure BDA0005146609090000041
  • Figure BDA0005146609090000042
    Figure BDA0005146609090000042
  • Figure BDA0005146609090000081
    Figure BDA0005146609090000081
Patent Text Reader

Abstract

The invention relates to a composite ceramic substrate with a core-shell structure and a preparation method thereof, and the preparation method comprises the following steps: carrying out ball milling, drying and high-temperature molten salt reaction on a metal oxide, TiO2, absolute ethyl alcohol and NaCl-KCl molten salt to synthesize titanate precursor powder; washing the titanate precursor powder, and adding deionized water to obtain a titanate aqueous solution; the preparation method comprises the following steps: uniformly mixing a surfactant, a cosurfactant, an oil phase and a titanate aqueous solution to obtain a first microemulsion; ammonia water is dripped into the first microemulsion, and a second microemulsion is obtained; adding isopropyl alcohol salt into the second microemulsion to obtain core-shell structure powder; demulsifying the core-shell structure powder with a demulsifier, drying and calcining, and ball-milling with zirconium balls, a solvent, a defoaming agent and a dispersing agent to obtain slurry; and degumming and sintering the slurry green body to prepare the ceramic substrate with the core-shell structure. The core-shell structure multiphase ceramic substrate prepared by the invention has the advantages of low dielectric loss, high breakdown strength and low sintering temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of microwave dielectric ceramics for the electronics industry and relates to a core-shell structured composite ceramic substrate and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of modern communication technologies such as mobile communications, satellite communications, global satellite positioning systems (GPS), Bluetooth technology, and wireless local area networks (WLAN), microwave technology is moving towards higher frequencies, that is, towards millimeter waves and submillimeter waves. The operating frequency of microwave communication devices is also constantly expanding to the high-frequency end, which puts higher requirements on the performance of microwave dielectric materials. Among them, miniaturization and integration have become new themes in the development of wireless communication systems and terminals. This requires microwave dielectric materials to have low dielectric loss and high breakdown strength.

[0003] Microwave dielectric ceramics have large dielectric loss and low breakdown strength, which limits their practical application. In order to expand their application areas, the dielectric properties of microwave dielectric ceramics are regulated by means of compounding with materials with low dielectric constant and negative temperature coefficient. However, due to the influence of intrinsic loss in the composite ceramic lattice and non-intrinsic loss such as grain size, second phase, impurities, defects, pores, etc. inside the material, the dielectric loss of the composite ceramics is high and the breakdown strength is low, which affects the expansion of the application field of the composite ceramics. Therefore, reducing the dielectric loss of composite ceramics and improving the breakdown strength is an urgent and significant topic.

[0004] Most existing methods for preparing composite ceramics are solid-phase methods. At present, most studies use the solid-phase method, which is to mix multi-phase ceramic powders in a set ratio by ball milling and sintering. However, the traditional solid-phase method has a high sintering temperature, uneven mixing, possible segregation after sintering, high porosity, large grain size, and easy introduction of impurities. It is obviously difficult to meet the application requirements of electronic components for miniaturization, micro-miniaturization and high performance. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for preparing a core-shell structured composite ceramic substrate with low dielectric loss and improved breakdown strength.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a core-shell structure composite ceramic substrate comprises the following steps:

[0008] (1) Using metal oxide and TiO2 as raw materials, using anhydrous ethanol as a medium, and using NaCl-KCl as a molten salt for the first ball milling, drying the slurry, and reacting the molten salt at a high temperature at a first preset temperature to synthesize titanate precursor powder;

[0009] (2) ultrasonically cleaning the titanate precursor powder with deionized water to remove NaCl and KCl, cleaning until no precipitation is found after titration with AgNO3 solution, and then drying to obtain titanate powder; stirring and mixing the titanate powder with deionized water to form a titanate aqueous solution;

[0010] (3) uniformly mixing the surfactant, the co-surfactant, the oil phase and the titanate aqueous solution to obtain a first microemulsion;

[0011] (4) dropping ammonia water into the first microemulsion to obtain a second microemulsion;

[0012] (5) adding metal isopropoxide to the second microemulsion, and performing ultrasonic dispersion at a second preset temperature for a first preset time to generate a core-shell structure powder having a metal hydroxide shell, thereby obtaining a third microemulsion;

[0013] (6) Demulsifying the third microemulsion containing the core-shell structure powder with a demulsifier at a third preset temperature, precipitating after ultrasonic dispersion, and centrifugally washing to remove the active agent on the particle surface to obtain a composite powder, drying the composite powder and placing it in a tubular furnace, and calcining it under an inert gas atmosphere to obtain a ceramic powder with a core-shell structure;

[0014] (7) Ceramic powder, zirconium balls, solvent, defoamer, dispersant and binder are added to a ball mill in proportion, and the mixture is sieved after a certain period of ball milling for the second time, and then vacuum-defoamed to obtain a slurry;

[0015] (8) After the slurry is tape-cast, it is cut into green bodies of certain specifications and sizes, and the green bodies are debinded and microwave sintered to form a ceramic substrate with a core-shell structure.

[0016] The metal oxide is selected from at least one of calcium oxide, barium oxide, magnesium oxide and strontium oxide; the first preset temperature is 900-1100° C., and the high-temperature molten salt reaction time is 1-2 hours.

[0017] The molar ratio of the metal oxide to TiO2 is 1:(0.5-4.5), the time of the first ball milling is 6-10 hours, and the rotation speed of the first ball milling is 200-400 r / min; the volume mass ratio of the anhydrous ethanol to the raw material is (2-3):1, the mass ratio of the molten salt to the raw material is (3-10):1, the mass ratio of NaCl to KCl is (1-2):1, the time of drying the slurry is 16-24 hours, and the temperature of drying the slurry is 50-60°C;

[0018] The drying time in step (2) is 16 to 24 hours, the drying temperature is 50 to 60° C., the ultrasonic cleaning of the titanate precursor powder is carried out at a temperature of 25 to 35° C., a time of 20 to 30 minutes, a frequency of 20 to 40 KHz, and a power of 120 to 300 W, and the concentration of the AgNO3 solution is 0.01 to 1 mol / L;

[0019] The molar concentration of the titanate aqueous solution is 0.5-1 mol / L.

[0020] The surfactant is selected from at least one of sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, sorbitan monostearate, octadecenoic acid, polyoxyethylene sorbitan monooleate and nonylphenol polyoxyethylene ether; the co-surfactant is selected from at least one of n-hexanol, n-pentanol and n-octanol; the oil phase is selected from at least one of cyclohexane, n-heptane and isooctane, the mass ratio of the surfactant to the oil phase is 3:7, 4:6, 5:5, 6:4 or 7:3, the mass ratio of the surfactant to the co-surfactant is 1:4, 2:3, 3:2 or 4:1, and the mass ratio of the surfactant to the titanate aqueous solution is 3:7, 4:6, 5:5, 6:4 or 7:3;

[0021] The surfactant, the co-surfactant, the oil phase and the titanate aqueous solution are uniformly mixed by ultrasound;

[0022] The ammonia water is dripped into the first microemulsion under ultrasonic dispersion at a temperature of 25-35°C, a time of 20-30 minutes, a frequency of 20-40 KHz, and a power of 120-300 W;

[0023] The pH value of the second microemulsion is 8-9.

[0024] The metal isopropoxide is samarium isopropoxide, cerium isopropoxide, copper isopropoxide, neodymium isopropoxide, aluminum isopropoxide or zinc isopropoxide; the molar ratio of the metal isopropoxide to the titanate solution is 7:4, 6:5, 5:6, 4:7 or 3:8;

[0025] The first preset time is 10 to 16 hours, and the second preset temperature is 20 to 100°C.

[0026] The frequency of ultrasonic dispersion at the second preset temperature is 20-40 KHz, and the power is 120-300W.

[0027] The demulsifier is selected from at least one of acetone, ethyl cellulose, chitosan, α-amylase and β-cyclodextrin; the mass ratio of the demulsifier to the third microemulsion is (0.4-2):1, and the third preset temperature is 20-80°C;

[0028] The ultrasonic dispersion is performed at a third preset temperature for 10 to 30 minutes, at a frequency of 20 to 40 kHz, and at a power of 120 to 300 W;

[0029] The centrifugal speed is 5000-10000 r / min, and the centrifugal time is 5-15 min;

[0030] The composite powder is dried at a temperature of 50 to 60° C. and for a drying time of 4 to 8 hours.

[0031] The calcination temperature is 500-1000°C, and the calcination time is 1-2h;

[0032] The inert gas is Ar gas or nitrogen gas.

[0033] The mass fraction of the ceramic powder is 35-50%, the mass fraction of the solvent is 20-25%, the mass fraction of the defoamer is 0-5%, the mass fraction of the dispersant is 14-16%, and the mass fraction of the binder is 15-28%;

[0034] The solvent is methyl ethyl ketone, toluene, xylene, isopropanol, ethanol, acetone or ethyl acetate;

[0035] The defoaming agent is emulsified silicone oil, n-butanol, tributyl phosphate or n-octanol;

[0036] The dispersant is triethanolamine, ammonium citrate, polyvinyl pyrrolidone or polyacrylic acid salt;

[0037] The binder is carboxyethyl cellulose, polyvinyl alcohol, latex or methyl cellulose;

[0038] The mass ratio of the ceramic powder to the zirconium ball is 1:(2-3), the rotation speed of the second ball milling is 150-200 r / min, the time of the second ball milling is 14-24 hours, and the sieve mesh number is 300-500 meshes.

[0039] The binder removal curve of the green body of the ceramic substrate is:

[0040]

[0041] RT is the room temperature during debinding; T1 is 200-400℃; T2 is 900-1000℃.

[0042] The microwave sintering heating curve of the debinded green body is:

[0043]

[0044] Among them, RT is the room temperature during microwave sintering; T3 is the relatively low temperature section temperature; T4 is the microwave sintering temperature; T3 is 200°C-400°C, and T4 is 1100°C-1150°C.

[0045] The green bodies are stacked in piles of 1 to 2 pieces, with zirconium oxide powder spread between the pieces, and placed on a support plate in a flat form for debinding. After debinding, the green bodies are stacked in piles of 1 to 5 pieces, with zirconium oxide powder spread between the pieces, and placed on a support plate in a flat form with a load of 300 to 500 g for sintering.

[0046] The ceramic powder and the composite ceramic substrate have a core-shell structure after debinding and sintering, the shell of the core-shell structure is samarium oxide, cerium oxide, copper oxide, neodymium oxide, aluminum oxide or zinc oxide, the shell thickness is 5 to 20 nm, the crystal core is at least one of calcium titanate, magnesium titanate, barium titanate and strontium titanate crystals, and the average grain size is 1 to 2 μm;

[0047] The size of the cut green body is (50.8±0.2)×(50.8±0.2)×(0.9±0.1 mm).

[0048] The present invention also provides a core-shell structured composite ceramic substrate, which is prepared according to the preparation method.

[0049] By means of the above technical solution, the present invention has at least the following advantages:

[0050] 1. A composite ceramic substrate prepared by the present invention has low dielectric loss and high quality factor. The core-shell process can greatly improve the dielectric properties of high dielectric constant composite ceramic substrates. The core particles are surrounded by shells to form a barrier layer. Because the shell localizes the charge carriers, the loss tangent is reduced and the conductivity is reduced, thereby reducing the dielectric loss of the composite ceramic substrate. The dielectric loss of the sample is tested by the resonant cavity method. Taking calcium titanate ceramic substrate as an example, under the condition of frequency 1kHz, it is reduced from the original 2% to about 0.2%;

[0051] 2. A composite ceramic substrate prepared by the present invention has high breakdown strength. In view of the core-shell structure characteristics of the composite ceramic substrate, the present invention can effectively control the thickness and composition of the shell, the size and uniformity of the crystal nucleus, and the dispersion of the powder by controlling the molar ratio of pure metal oxide and TiO2 in the reaction process, the reaction temperature of the titanate molten salt, the composition and ratio of the surfactant, the co-surfactant, the oil phase, and the water phase, the isopropoxide composition and addition amount of the metal, the synthesis temperature and insulation time of the shell oxide, the composition and ratio of the demulsifier, the sintering temperature and other parameters, reduce the pores of the ceramic material, and the probability of containing impurities, thereby improving the breakdown strength of the composite ceramic substrate after microwave sintering. Taking the calcium titanate ceramic substrate as an example, the breakdown strength is increased from the original 300kV / cm to about 500kV / cm.

[0052] 3. The composite ceramic substrate prepared by the present invention has a low sintering temperature. In view of the high sintering temperature of the composite ceramic substrate, a ceramic powder with high surface activity is synthesized by a core-shell process of a wet chemical method, and a ceramic substrate is prepared by microwave sintering to maintain the crystal morphology of the ceramic substrate, thereby reducing the sintering temperature. Taking a calcium titanate ceramic substrate as an example, the sintering temperature is reduced from the original 1200°C to 1150°C.

[0053] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION

[0054] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.

[0055] Example 1

[0056] A method for preparing a core-shell structure composite ceramic substrate comprises the following steps:

[0057] (1) Using analytically pure calcium oxide and TiO2 as raw materials, anhydrous ethanol as a medium, and NaCl-KCl as a molten salt, ball milling at 300 r / min for 8 hours, drying at a temperature of 50°C for 16 hours, drying the slurry, and reacting the high-temperature molten salt at 1000°C for 1.5 hours to synthesize calcium titanate precursor powder; the molar ratio of calcium oxide to TiO2 is 1:1, the volume mass ratio of the anhydrous ethanol to the raw material is 2:1, the mass ratio of the molten salt to the raw material is 3:1, and the mass ratio of NaCl to KCl in the molten salt is 1:1;

[0058] (2) ultrasonically cleaning the calcium titanate precursor powder with deionized water at a temperature of 25° C., a time of 20 min, a frequency of 20 KHz, and a power of 120 W to remove NaCl and KCl, cleaning until no precipitation is found after titration with a 0.02 mol / L AgNO3 solution, and drying at a temperature of 50° C. for 24 h to obtain calcium titanate powder; stirring and mixing the calcium titanate powder with deionized water to form a calcium titanate aqueous solution with a concentration of 0.5 mol / L;

[0059] (3) uniformly mixing the surfactant sodium dodecyl sulfate, the auxiliary surfactant n-hexanol, the oil phase cyclohexane and the calcium titanate aqueous solution by ultrasonic dispersion to obtain a first microemulsion; wherein the mass ratio of the surfactant sodium dodecyl sulfate to the auxiliary surfactant n-hexanol is 1:4, the mass ratio of sodium dodecyl sulfate to cyclohexane is 3:7, and the mass ratio of sodium dodecyl sulfate to the titanate aqueous solution is 3:7, and the ultrasonic dispersion is carried out at a temperature of 25°C, a time of 20 min, a frequency of 20 kHz, and a power of 120 W;

[0060] In this step, the hydrophilic end of the surfactant combines with water, while the lipophilic end of the surfactant combines with the solvent oil. Under the action of the co-surfactant, the surfactant forms spherical micelles in which the oil phase encloses the water phase, and the water phase of the spherical micelles contains the titanate core.

[0061] (4) dropping ammonia water into the first microemulsion, and performing ultrasonic dispersion at a temperature of 25° C., a time of 20 min, a frequency of 20 kHz, and a power of 120 W to obtain a second microemulsion with a pH value of 8;

[0062] (5) adding samarium isopropoxide to the second microemulsion, and performing ultrasonic dispersion at a temperature of 60° C., a time of 13 h, a frequency of 20 kHz, and a power of 120 W to obtain a third microemulsion containing a core-shell structure;

[0063] In this step, the solubility of samarium isopropoxide in the oil phase is relatively large, and samarium isopropoxide can be fully dispersed in the microemulsion oil phase and fully contacted with the dispersed micelles. The samarium isopropoxide molecules pass through the surfactant membrane layer from the oil phase and diffuse into the water phase. Under the catalysis of ammonia water in the water phase, they are fully hydrolyzed and polycondensed, and finally wrapped on the surface of the calcium titanate core to generate a core-shell structure powder with a samarium hydroxide shell.

[0064] The molar ratio of samarium isopropoxide to calcium titanate aqueous solution is 7:4;

[0065] (6) Demulsifying the third microemulsion containing the core-shell structure with demulsifier acetone at 60° C., with the mass ratio of acetone to the third microemulsion being 0.4:1, and ultrasonically dispersing for 10 min at a frequency of 20 kHz and a power of 120 W. After ultrasonic dispersion, a precipitate is precipitated to obtain a mixed solution, which is centrifuged at a speed of 5000 r / min for 5 min. The mixed solution is washed with ethanol to remove the active agent on the particle surface to obtain a composite powder. After drying the composite powder at 60° C. for 4 h, the composite powder is placed in a tubular furnace and calcined at 800° C. for 1.5 h under an Ar atmosphere to obtain a ceramic powder with a core-shell structure;

[0066] (7) Ceramic powder, zirconium balls, solvent, defoamer, dispersant, and binder are added to a ball mill in a proportion such that the mass ratio of ceramic powder to zirconium balls is 1:2. The mixture is ball milled at 150 r / min for 16 h, passed through a 400-mesh sieve, and vacuum-defoamed to obtain a slurry.

[0067] The mass fraction of the ceramic powder is 35%, the mass fraction of the solvent methyl ethyl ketone is 25%, the mass fraction of the defoaming agent emulsified silicone oil is 5%, the mass fraction of the dispersant triethanolamine is 15%, and the mass fraction of the binder carboxyethyl cellulose is 20%;

[0068] (8) After the slurry is tape-cast, it is cut into green pieces with a specification of 50.8×50.8×0.9 mm.

[0069] Two green sheets are stacked in a pile, zirconium oxide powder is spread between the sheets, and the green sheets are placed on a support plate in a flat manner for debinding. Three green sheets after debinding are stacked in a pile, zirconium oxide powder is spread between the sheets, and the green sheets are placed on a support plate in a flat manner with a load of 300 to 500 g for sintering. After debinding and microwave sintering, the green sheets are made into a ceramic substrate with a core-shell structure, wherein the shell of the core-shell structure is samarium oxide with a shell thickness of 20 nm, the crystal core is calcium titanate crystal, and the average grain size is 1 μm;

[0070] The binder removal curve of the green compact is:

[0071] Temperature heating rate holding time

[0072] RT~T1 5℃ / min /

[0073]

[0074] RT is the room temperature during debinding; T1 is 300℃; T2 is 950℃;

[0075] The sintering temperature rise curve of the debinded green body is:

[0076]

[0077] Among them, RT is the room temperature during sintering; T3 is the relatively low temperature section temperature; T4 is the sintering temperature; T3 is 300°C, and T4 is 1100°C.

[0078] Example 2

[0079] A method for preparing a core-shell structure composite ceramic substrate comprises the following steps:

[0080] (1) Using analytically pure strontium oxide and TiO2 as raw materials, anhydrous ethanol as a medium, and NaCl-KCl as a molten salt, ball milling at 400 r / min for 10 hours, drying the slurry at a temperature of 55°C for 20 hours, and reacting the high-temperature molten salt at 1100°C for 1 hour to synthesize strontium titanate precursor powder; the molar ratio of strontium oxide to TiO2 is 1:2, the volume mass ratio of the anhydrous ethanol to the raw material is 2.5:1, the mass ratio of the molten salt to the raw material is 5:1, and the mass ratio of NaCl to KCl in the molten salt is 1.5:1;

[0081] (2) ultrasonically cleaning the strontium titanate precursor powder with deionized water at a temperature of 30°C, a time of 25 min, a frequency of 25 kHz, and a power of 180 W to remove NaCl and KCl, cleaning until no precipitation is produced by titration with a 0.05 mol / L AgNO3 solution, drying at a temperature of 55°C for 20 h, and drying to obtain strontium titanate powder; stirring and mixing the strontium titanate powder with deionized water to form a 0.8 mol / L strontium titanate aqueous solution;

[0082] (3) uniformly mixing the surfactant, the co-surfactant, the oil phase and the strontium titanate aqueous solution by ultrasonic dispersion to obtain a first emulsion; wherein the mass ratio of the surfactant to the co-surfactant is 2:3, the mass ratio of the surfactant to the oil phase is 5:5, and the mass ratio of the surfactant to the titanate aqueous solution is 5:5; the ultrasonic dispersion is carried out at a temperature of 30° C., a time of 25 min, a frequency of 25 kHz, and a power of 180 W;

[0083] The surfactant is a mixture of cetyltrimethylammonium bromide and nonylphenol polyoxyethylene ether in any proportion;

[0084] The co-surfactant is a mixture of n-pentanol and n-octanol in any proportion;

[0085] The oil phase is isooctane;

[0086] (4) Under ultrasonic dispersion at a temperature of 30° C., a time of 25 min, a frequency of 25 kHz, and a power of 180 W, ammonia water was dropped into the first microemulsion to obtain a second microemulsion with a pH value of 9;

[0087] (5) adding copper isopropoxide to the second microemulsion, and performing ultrasonic dispersion for 10 h at a temperature of 100° C., a frequency of 30 kHz, and a power of 200 W to obtain a third microemulsion containing a core-shell structure;

[0088] In this step, copper isopropoxide has a large solubility in the oil phase, and can be fully dispersed in the microemulsion oil phase and fully contacted with the dispersed micelles. The copper isopropoxide molecules pass through the surfactant membrane layer from the oil phase and diffuse into the water phase. Under the catalysis of ammonia water in the water phase, they are fully hydrolyzed and polycondensed, and finally wrapped on the surface of the strontium titanate core to generate a core-shell structure powder with a copper hydroxide shell.

[0089] The molar ratio of the copper isopropoxide to the strontium titanate aqueous solution is 6:5;

[0090] (6) The third microemulsion containing a core-shell structure is demulsified with a demulsifier chitosan at 80°C, and ultrasonically dispersed at a frequency of 25KHz and a power of 180W for 20 minutes. After ultrasonic dispersion, a precipitate is precipitated to obtain a mixed solution, which is centrifuged at a speed of 7000r / min for 10 minutes. The mixed solution is washed with ethanol to remove the active agent on the surface of the particles to obtain a composite powder. The composite powder is dried at a temperature of 55°C for 6 hours, placed in a tubular furnace, and calcined at 500°C for 2 hours under a nitrogen atmosphere to obtain a ceramic powder with a core-shell structure; the mass ratio of chitosan to the third microemulsion is 1:1;

[0091] (7) Ceramic powder, zirconium balls, solvent, defoamer, dispersant, and binder are added to a ball mill in a proportion such that the mass ratio of ceramic powder to zirconium balls is 1:2.5. The mixture is ball milled at 180 r / min for 20 h, passed through a 300-mesh sieve, and vacuum-defoamed to obtain a slurry.

[0092] The mass fraction of the ceramic powder is 40%, the mass fraction of the solvent methyl ethyl ketone is 22%, the mass fraction of the defoaming agent emulsified silicone oil is 1%, the mass fraction of the dispersant triethanolamine is 16%, and the mass fraction of the binder carboxyethyl cellulose is 21%;

[0093] The solvent is isopropanol;

[0094] The defoaming agent is n-butanol;

[0095] The dispersant is polyacrylate;

[0096] The binder is methyl cellulose;

[0097] (8) After the slurry is tape-cast, it is cut into green pieces with a specification of 50.6×50.6×0.8 mm.

[0098] The green bodies are stacked one piece at a time, and are placed on a support plate in a flat manner for debinding. After debinding, 5 green bodies are stacked in a time, and zirconium oxide powder is spread between the sheets. The green bodies are placed on a support plate in a flat manner with a load of 300 to 500 g for sintering. After debinding and microwave sintering, the green bodies are made into a ceramic substrate with a core-shell structure, wherein the shell of the core-shell structure is copper oxide with a shell thickness of 15 nm, and the crystal core is strontium titanate crystal with an average grain size of 1.5 μm.

[0099] The binder removal curve of the green compact is:

[0100]

[0101] RT is the room temperature during debinding; T1 is 200℃; T2 is 900℃;

[0102] The sintering temperature rise curve of the debinded green body is:

[0103]

[0104] Among them, RT is the room temperature during sintering; T3 is the relatively low temperature section temperature; T4 is the sintering temperature; T3 is 400°C, and T4 is 1125°C.

[0105] Example 3

[0106] A method for preparing a core-shell structure composite ceramic substrate comprises the following steps:

[0107] (1) Using the analyzed metal oxides and TiO2 as raw materials, anhydrous ethanol as the medium, and NaCl-KCl as the molten salt in a mass ratio of 2:1, ball milling was performed at 200 r / min for 6 hours, the slurry was dried at a temperature of 60°C for 24 hours, and the high-temperature molten salt was reacted at 900°C for 2 hours to synthesize titanate precursor powder; the molar ratio of metal oxide to TiO2 was 1:4, the volume mass ratio of the anhydrous ethanol to the raw material was 3:1, the mass ratio of the molten salt to the raw material was 10:1, and the mass ratio of NaCl to KCl in the molten salt was 2:1;

[0108] The metal oxide is a mixture of barium oxide and magnesium oxide in any proportion;

[0109] (2) ultrasonically cleaning the titanate precursor powder with deionized water, wherein the ultrasonic cleaning temperature of the strontium titanate precursor is 35°C, the time is 30 min, the frequency is 40 KHz, and the power is 300 W to remove NaCl and KCl, and cleaning is performed until no precipitation is found after titration with a 1.0 mol / L AgNO3 solution, and then drying at 60°C for 24 h to obtain titanate powder; stirring and mixing the titanate powder with deionized water to form a 1.0 mol / L titanate aqueous solution;

[0110] (3) The surfactant sodium dodecyl sulfate, the co-surfactant, the oil phase and the titanate aqueous solution are uniformly mixed by ultrasonic dispersion to obtain a first microemulsion; the mass ratio of the surfactant to the co-surfactant is 4:1, the mass ratio of the surfactant to the oil phase is 7:3, the mass ratio of the surfactant to the titanate aqueous solution is 7:3, the ultrasonic dispersion temperature is 35°C, the time is 30 minutes, the frequency is 40KHz, and the power is 300W;

[0111] The surfactant is a mixture of octadecenoic acid, sorbitan monostearate and sodium dodecyl sulfate in any proportion;

[0112] The co-surfactant is a mixture of n-hexanol, n-pentanol and n-octanol in any proportion;

[0113] The oil phase is a mixture of cyclohexane and n-heptane in any proportion;

[0114] (4) ultrasonically dispersing the solution at a temperature of 35° C., a time of 30 min, a frequency of 40 kHz, and a power of 300 W, and dripping ammonia water into the first microemulsion to obtain a second microemulsion with a pH value of 8;

[0115] (5) Aluminum isopropoxide is added to the second microemulsion, and ultrasonic dispersion is performed at a temperature of 20° C., a frequency of 40 kHz, and a power of 300 W for 16 hours. Aluminum isopropoxide has a large solubility in the oil phase, and can be fully dispersed in the microemulsion oil phase and fully contact with the dispersed micelles. Aluminum isopropoxide molecules penetrate and diffuse from the oil phase through the surfactant membrane layer to the aqueous phase. Under the catalysis of ammonia water in the aqueous phase, they are fully hydrolyzed and polycondensed, and finally wrapped on the surface of the titanate core to generate a core-shell structure powder with a metal aluminum hydroxide shell, thereby forming a third microemulsion;

[0116] The molar ratio of the aluminum isopropoxide to the titanate aqueous solution is 3:8;

[0117] (6) Demulsifying the third microemulsion containing a core-shell structure with a demulsifier at 20° C., ultrasonically dispersing for 30 minutes at a frequency of 40 kHz and a power of 300 W, until a precipitate is precipitated to obtain a mixed solution, centrifuging at 10,000 r / min for 15 minutes, washing the mixed solution with ethanol to remove the active agent on the particle surface to obtain a composite powder, drying the composite powder at 60° C. for 8 hours, placing it in a tubular furnace, and calcining it at 1,000° C. for 1 hour under an Ar atmosphere to obtain a ceramic powder with a core-shell structure; the demulsifier is a mixture of ethyl cellulose, α-amylase and β-cyclodextrin in any proportion; the mass ratio of the demulsifier mixture to the third microemulsion is 2:1;

[0118] (7) Ceramic powder, zirconium balls, solvent, defoamer, dispersant, and binder are added to a ball mill in a proportion such that the mass ratio of ceramic powder to zirconium balls is 1:3. The mixture is ball milled at 200 r / min for 24 h, passed through a 500-mesh sieve, and vacuum-defoamed to obtain a slurry.

[0119] The mass fraction of the ceramic powder is 50%, the mass fraction of the solvent methyl ethyl ketone is 20%, the mass fraction of the defoaming agent emulsified silicone oil is 1%, the mass fraction of the dispersant triethanolamine is 14%, and the mass fraction of the binder carboxyethyl cellulose is 15%;

[0120] The solvent is toluene;

[0121] The defoamer is n-octanol;

[0122] The dispersant is ammonium citrate;

[0123] The binder is polyvinyl alcohol;

[0124] (8) After the slurry is tape-cast, it is cut into green pieces with a size of 60×60×1 mm.

[0125] Two green sheets are stacked in a pile, zirconium oxide powder is spread between the sheets, and the green sheets are placed on a sintering plate in a flat manner for debinding. Four green sheets after debinding are stacked in a pile, zirconium oxide powder is spread between the sheets, and the green sheets are placed on a sintering plate in a flat manner with a load of 300 to 500 g. After debinding and microwave sintering, the green sheets are made into a ceramic substrate with a core-shell structure, wherein the shell of the core-shell structure is aluminum oxide with a shell thickness of 10 nm, the crystal core is barium titanate and magnesium titanate crystals, and the average grain size is 2 μm.

[0126] The binder removal curve of the green compact is:

[0127]

[0128] RT is the room temperature during debinding; T1 is 400℃; T2 is 1000℃;

[0129] The sintering temperature rise curve of the debinded green body is:

[0130]

[0131]

[0132] Among them, RT is the room temperature during sintering; T3 is the relatively low temperature section temperature; T4 is the sintering temperature; T3 is 200°C, and T4 is 1150°C.

[0133] Table 1 Performance comparison between each embodiment and existing magnesium titanate ceramic substrate

[0134] Project Name Dielectric loss % Breakdown strength kV / cm Sintering temperature℃ Example 1 0.2 500 1100 Example 2 0.7 389 1125 Example 3 1.0 355 1150 Existing calcium titanate ceramic substrate 2 300 1200

[0135] Among them, the dielectric loss is tested at a frequency of 1kHz, and the insulation resistivity is tested at 500V.

[0136] It can be seen from the performance test indicators in Table 1 that the various performance indicators of Example 1 are the best. The shell thickness of the core-shell structure powder synthesized in Example 1 is the largest, and the shell surrounds the core particles to form a barrier layer. The shell localizes the charge carriers, reduces the loss tangent and reduces the electrical conductivity, thereby reducing the dielectric loss of the composite ceramic substrate; at the same time, it reduces the pores and the probability of containing impurities in the ceramic material, thereby improving the breakdown strength of the composite ceramic substrate after sintering; Example 1 synthesizes ceramic powder with high surface activity through a core-shell process by a wet chemical method, prepares a ceramic substrate by microwave sintering, and maintains the crystal morphology of the ceramic substrate, thereby reducing the sintering temperature.

[0137] The formation mechanism of the core-shell structured composite ceramic substrate of the present invention is as follows: titanium dioxide and metal oxides are ball-milled and mixed to synthesize titanate powder under NaCl-KCl molten salt conditions, and the molten salt acts as a flux and a reaction medium. The surfactant, co-surfactant, oil phase, and titanate aqueous solution are uniformly mixed, the hydrophilic end of the surfactant is combined with water, and the lipophilic end of the surfactant is combined with the solvent oil. Under the action of the co-surfactant, the surfactant forms oil-in-water spherical micelles, and the aqueous phase of the spherical micelles contains the titanate core. Since there are gaps in the surfactant layer surrounding the aqueous dispersed phase, and there is rapid molecular exchange between the aqueous phase and the oil phase, when ammonia water is dripped into the microemulsion, the ammonia water collides with the spherical micelles and enters the aqueous phase of the micelles. The solubility of isopropyl alcohol salt in the oil phase is relatively large, and the isopropyl alcohol salt in the microemulsion oil phase is relatively large. The isopropyl alcohol salt molecules will pass through the surfactant membrane layer from the oil phase and diffuse into the water core under certain conditions. Under the catalysis of ammonia water, they will be fully hydrolyzed and polycondensed, and finally wrapped on the surface of the titanate core to form a metal hydroxide as the shell of the core-shell structure. Subsequently, a demulsifier is added to destroy the surfactant micelle structure, and a composite powder is obtained after centrifugal washing. The metal hydroxide on the surface of the crystal core in the composite powder is calcined to form a core-shell structure with a metal oxide as the shell and a titanate as the core. The structure is maintained after subsequent debinding and microwave sintering.

[0138] The present invention utilizes a liquid phase method and a core-shell process to synthesize a composite ceramic substrate having a core-shell structure. The process is carried out in a liquid phase to achieve uniform mixing at the atomic / molecular level, and can achieve better distribution of additives in the composite ceramic by using a low amount of additives, thereby better controlling the size of grain boundaries and grains. The chemical composition can also be precisely controlled and the sintering temperature can be reduced, ultimately reducing the dielectric loss of the substrate and improving the breakdown strength, and a composite ceramic substrate with low dielectric loss, high breakdown strength, and low sintering temperature can be obtained.

[0139] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a core-shell structured composite ceramic substrate, characterized in that: The following steps are involved: (1) Using metal oxide and TiO2 as raw materials, using anhydrous ethanol as a medium, and using NaCl-KCl as a molten salt for the first ball milling, drying the slurry, and reacting the molten salt at a high temperature at a first preset temperature to synthesize titanate precursor powder; (2) ultrasonically cleaning the titanate precursor powder with deionized water to remove NaCl and KCl, cleaning until no precipitation is found after titration with AgNO3 solution, and then drying to obtain titanate powder; stirring and mixing the titanate powder with deionized water to form a titanate aqueous solution; (3) uniformly mixing the surfactant, the co-surfactant, the oil phase and the titanate aqueous solution to obtain a first microemulsion; (4) dropping ammonia water into the first microemulsion to obtain a second microemulsion; (5) adding metal isopropoxide to the second microemulsion, and performing ultrasonic dispersion at a second preset temperature for a first preset time to generate a core-shell structure powder having a metal hydroxide shell, thereby obtaining a third microemulsion; (6) demulsifying the third microemulsion containing the core-shell structure with a demulsifier at a third preset temperature, precipitating after ultrasonic dispersion, centrifugally washing to remove the active agent on the particle surface, obtaining a composite powder, drying the composite powder, placing it in a tubular furnace, and calcining it under an inert gas atmosphere to obtain a ceramic powder with a core-shell structure; (7) Ceramic powder, zirconium balls, solvent, defoamer, dispersant and binder are added to a ball mill in proportion, and the mixture is sieved after a certain period of ball milling for the second time, and then vacuum-defoamed to obtain a slurry; (8) After the slurry is tape-cast, it is cut into green bodies of certain specifications and sizes, and the green bodies are debinded and microwave sintered to form a ceramic substrate with a core-shell structure.

2. The preparation method according to claim 1, characterized in that: The metal oxide is selected from at least one of calcium oxide, barium oxide, magnesium oxide and strontium oxide; the first preset temperature is 900-1100° C., and the high-temperature molten salt reaction time is 1-2 hours.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the metal oxide to TiO2 is 1:(0.5-4.5), the time of the first ball milling is 6-10 hours, and the rotation speed of the first ball milling is 200-400 r / min; the volume mass ratio of the anhydrous ethanol to the raw material is 2-3:1, the mass ratio of the molten salt to the raw material is (3-10):1, the mass ratio of NaCl to KCl is (1-2):1, the time of drying the slurry is 16-24 hours, and the temperature of drying the slurry is 50-60°C; The drying time in step (2) is 16 to 24 hours, the drying temperature is 50 to 60° C., the ultrasonic cleaning of the titanate precursor powder is carried out at a temperature of 25 to 35° C., a time of 20 to 30 minutes, a frequency of 20 to 40 KHz, and a power of 120 to 300 W, and the molar concentration of the AgNO3 solution is 0.01 to 1 mol / L; The molar concentration of the titanate aqueous solution is 0.5-1 mol / L.

4. The preparation method according to claim 3, characterized in that: The surfactant is selected from at least one of sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, sorbitan monostearate, octadecenoic acid, polyoxyethylene sorbitan monooleate and nonylphenol polyoxyethylene ether; the co-surfactant is selected from at least one of n-hexanol, n-pentanol and n-octanol; the oil phase is selected from at least one of cyclohexane, n-heptane and isooctane, the mass ratio of the surfactant to the oil phase is 3:7, 4:6, 5:5, 6:4 or 7:3, the mass ratio of the surfactant to the co-surfactant is 1:4, 2:3, 3:2 or 4:1, and the mass ratio of the surfactant to the titanate aqueous solution is 3:7, 4:6, 5:5, 6:4 or 7:3; The surfactant, the co-surfactant, the oil phase and the titanate aqueous solution are uniformly mixed by ultrasound; The ammonia water is dripped into the first microemulsion under ultrasonic dispersion at a temperature of 25-35°C, a time of 20-30 minutes, a frequency of 20-40 KHz, and a power of 120-300 W; The pH value of the second microemulsion is 8-9.

5. The preparation method according to claim 4, characterized in that: The metal isopropoxide is samarium isopropoxide, cerium isopropoxide, copper isopropoxide, neodymium isopropoxide, aluminum isopropoxide or zinc isopropoxide; the molar ratio of the metal isopropoxide to the titanate solution is 7:4, 6:5, 5:6, 4:7 or 3:8; The first preset time is 10 to 16 hours, and the second preset temperature is 20 to 100° C.; The frequency of ultrasonic dispersion at the second preset temperature is 20-40 KHz, and the power is 120-300W.

6. The preparation method according to claim 5, characterized in that: The demulsifier is selected from at least one of acetone, ethyl cellulose, chitosan, α-amylase and β-cyclodextrin; the mass ratio of the demulsifier to the third microemulsion is (0.4-2):1, and the third preset temperature is 20-80°C; The ultrasonic dispersion is performed at a third preset temperature for 10 to 30 minutes, at a frequency of 20 to 40 kHz, and at a power of 120 to 300 W; The centrifugal speed is 5000-10000 r / min, and the centrifugal time is 5-15 min; The composite powder is dried at a temperature of 50 to 60° C. and for a drying time of 4 to 8 hours. The calcination temperature is 500-1000°C, and the calcination time is 1-2h; The inert gas is Ar gas or nitrogen gas.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The mass fraction of the ceramic powder is 35-50%, the mass fraction of the solvent is 20-25%, the mass fraction of the defoamer is 0-5%, the mass fraction of the dispersant is 14-16%, and the mass fraction of the binder is 15-28%; The solvent is methyl ethyl ketone, toluene, xylene, isopropanol, ethanol, acetone or ethyl acetate; The defoaming agent is emulsified silicone oil, n-butanol, tributyl phosphate or n-octanol; The dispersant is triethanolamine, ammonium citrate, polyvinyl pyrrolidone or polyacrylic acid salt; The binder is carboxyethyl cellulose, polyvinyl alcohol, latex or methyl cellulose; The mass ratio of the ceramic powder to the zirconium ball is 1:(2-3), the rotation speed of the second ball milling is 150-200 r / min, the time of the second ball milling is 14-24 hours, and the sieve mesh number is 300-500 meshes.

8. The preparation method according to claim 7, characterized in that: The debinding curve of the green body of the ceramic substrate is: RT is the room temperature during debinding; T1 is 200-400℃; T2 is 900-1000℃; The microwave sintering heating curve of the debinded green body is: Among them, RT is the room temperature during microwave sintering; T3 is the relatively low temperature section temperature; T4 is the microwave sintering temperature; T3 is 200°C-400°C, and T4 is 1100°C-1150°C.

9. The preparation method according to claim 8, characterized in that: The green bodies are stacked in a pile of 1 to 2 pieces, zirconium oxide powder is spread between the pieces, and the green bodies are placed on a setter plate in a flat manner for debinding. After debinding, the green bodies are stacked in a pile of 1 to 5 pieces, zirconium oxide powder is spread between the pieces, and the green bodies are placed on a setter plate in a flat manner with a load of 300 to 500 g for sintering. The ceramic powder and the composite ceramic substrate have a core-shell structure after debinding and sintering, the shell of the core-shell structure is samarium oxide, cerium oxide, copper oxide, neodymium oxide, aluminum oxide or zinc oxide, the shell thickness is 5 to 20 nm, the crystal core is at least one of calcium titanate, magnesium titanate, barium titanate and strontium titanate crystals, and the average grain size is 1 to 2 μm; The size of the cut green body is (50.8±0.2)×(50.8±0.2)×(0.9±0.1 mm).

10. A core-shell structured composite ceramic substrate, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of wide-temperature, high-pressure-resistant and high-energy-density ceramic dielectric material

    CN103864435A

  • Composite microwave dielectric ceramic material and preparation method thereof

    CN113321496A

  • Strontium titanate-based ceramic material as well as preparation method and application thereof

    CN113773073A

  • NANO complex oxide doped dielectric ceramic material, preparation method thereof and multilayer ceramic capacitors made from the same

    US20090135546A1

Cited By

  • (TiZrHfNbTa) C single-phase high-entropy ceramic powder and preparation method thereof

    CN122010570A